Effect of traffic noise on sleep : a case study in Serdang Raya, Selangor, Malaysia. - Nadaraja, Bavani; Yap, Xin Wei; Abdullah, Ramdzani (Thai Society of Higher Eduction Institutes on Environment, 2010)
Traffic noise has been recognised as a serious threat to the quality of life in most industrialised nations. The rapid growth of towns, cities and population has increased the density of traffic. There are various effects of traffic noise on people and these effects are often interrelated. The most common yet serious problem is sleep disturbance. In this study field measurement and questionnaire survey were carried out to determine the overall noise level and the view and opinion of the residents on their sleep disturbance. As the LAeq was higher than the guideline values, contradictorily the survey results showed that most of the residents sleep time was not affected and they were not really annoyed by the traffic noise. This is mainly because most of the residents at the study area residing there for more than 19 years and this is sufficient enough to describe the pattern of outcome where most of the residents were get used with the traffic noise and they adapt it in their daily life as a norm. Yet, countermeasures such as construction of noise barrier are highly recommended to curb the chronic effects. So, a further study is required to establish this.